Quality provision in competitive health care markets: Individuals vs. teams - Johann Han; Nadja Kairies-Schwarz; Markus Vomhof (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
We investigate the quality provision behavior and its implications for the occurrence of collusion in competitive health care markets where providers are assumed to be altruistic towards patients. For this, we employ a laboratory experiment with a health care market framing where subjects decide on the quality levels for one of three competing hospitals respectively. We vary whether quality decisions within hospitals are made by individuals or teams. Realized monetary patient benefits go to real patients outside the lab. We find that degrees of cooperation quickly converge towards negative values implying absence of collusion and patient centered quality choices. Moreover, hospitals treat qualities as strategic complements and adjust their quality choice in the same direction as their competitors. The response magnitude for team markets is weaker. This is driven by the non-cooperative, or altruistic teams which tend to set qualities strategically independent. – – Wir untersuchen das Bereitstellungsverhalten von Qualität in wettbewerblichen Gesundheitsmärkten mit Anbietern, die altruistisch den Patienten gegenüber sind. Hierfür verwenden wir ein gesundheitsökonomisches Laborexperiment mit Märkten, in denen die Teilnehmer über das Qualitätsniveau als eines von drei im Wettbewerb stehenden Krankenhäusern entscheiden. Wir variieren, ob Entscheidungen im Krankenhaus individuell oder im Team getroffen werden. Die monetarisierten Patientennutzen gehen an reale Patienten außerhalb des Labors. Wir finden, dass der Grad an Kooperation schnell gegen negative Werte geht, was impliziert, dass es keine Kollusion und patientenorientierte Qualitätsentscheidungen gibt. Darüber hinaus behandeln Individuen Qualität als strategisches Komplement und passen ihre Qualitätswahl an die ihrer Wettbewerber in gleicher Richtung an. Das Ausmaß dieser Reaktion ist schwächer für Teammärkte. Dieser Effekt wird durch nicht-kooperative oder altruistische Teammärkte getrieben, die dazu neigen, ihre Qualitäten strategisch unabhängig zu wählen.
Keywords: C92; D03; D43; D64; I11; L13; 330; quality competition; health care markets; team decisions; altruism; laboratory experiment